Daniel Deronda - Eliot, George (London : Everymans, 2000)
After living in poor conditions, Oliver runs away to the streets of London, where he meets a gang of pickpockets. Soon his life is changed forever.
Based on the novel Oliver Twist by Charles Dickens.
Not viewed.
Executive producers, Timothy Burrill, Petr Moravec ; camera, Pawel Edelman ; editing, Herve de Luze ; music, Rachel Portman.
Ben Kingsley, Barney Clark, Jamie Foreman, Harry Eden, Leanne Rowe, Edward Hardwicke, Ian McNeice, Mark Strong, Jeremy Swift, Frances Cuka, Michael Heath, Gillian Hanna, Alun Armstrong, Andy De La Tour, Peter Copley, Liz Smith.
MPAA rating: PG-13.
Copyright Collection.
Keywords: Orphans -- Drama; Pickpockets -- Drama; Film adaptations; Melodramas (Motion pictures); Fiction films